REINFORCEMENT OF INDONESIA’S REGIONAL REPRESENTATIVES COUNCIL FOR A BETTER FUTURE OF THE INDONESIAN PEOPLE'S REPRESENTATIVE INSTITUTION - Nurlia, Elly; Santoso, Nanda Trio; Lokman, Asmidar; Mahpudin, Mahpudin; Wawan, Wawan; Widaningsih, Widaningsih (Department of Government, FISIP, Universitas Padjadjaran, 2024)
This study examines the dynamics of the formation of representative institutions in Indonesia with a focus on the role of the Regional Representative Council of the Republic of Indonesia (DPD RI) in a representative democratic system. Applying a qualitative method with a literature review approach and documentation analysis, this study explores the main challenges faced by DPD RI, including the limited authority that limits its contribution to the legislative process. The findings show that Indonesia's bicameral system creates a significant power imbalance between the House of Representatives (DPR) and DPD RI, with DPR's dominance hampering DPD RI's representative function. The implications of these findings confirm the need for reorganization of Indonesia's bicameral system through strengthening the authority of DPD RI. This reform is expected to create a fairer balance of power, ensure better representation for the regions, and support a more democratic and inclusive system of government.